Post micromachining of MPW based CMOSâMEMS comb resonator and its mechanical and thermal characterization - Dennis, J.O. (Springer Verlag, 2016)
In recent years micro electro mechanical system (MEMS) based micro resonant sensors have been given a lot of attention due to their potential as a platform for the development of many novel physical, chemical, and biological sensors. That is why this paper covers post processing of the structures fabricated through Multi-Project-Wafer using 0.35Â Âµm MIMOS CMOS technology with particular focus on dry etching of Si and SiO2 from the front side of CMOSâMEMS chip that is optimized using aluminum coated carrier wafer and achieved results are debris free as compared to photoresist coated carrier wafer. The device is etched through from the front side to avoid parasitic capacitances and squeeze film damping by keeping minimum size of the die. The etching of SiO2 as well as deep Si etch-through using the same plasma etcher (SS110A Tegal) is successfully demonstrated in this work. Finally, after the successful post CMOS micromachining of the device, resonance frequency i.e. 8164Â Hz and quality factor i.e. 51.34, is determined. The joule heating effect due to the passing of current through the central shuttle of the device is characterized. The maximum temperature close to the anchors of the comb resonator where the piezoresistors are located is determined through temperature coefficient of resistance measurement using PE-4RF type probe station and it is found to be 37.62Â Â°C. Â© 2015, Springer-Verlag Berlin Heidelberg.